Comparative effect of anthocyanin on proliferation and migration of human gingival fibroblasts in the absence or presence of nicotine - Sarina Azimian; Maryam Torshabi; Zeinab Rezaei Esfahrood (Journal of Advanced Periodontology and Implant Dentistry)
Background. Oral fibroblast malfunction can result in periodontal diseases. Nicotine can prolong the healing process as an irritant of oral tissues. Anthocyanins have been demonstrated to have potential benefits in preventing or treating smoking-related periodontal diseases. Cyanidin chloride’s (CC’s) potential in oral wound healing and the viability, proliferation, and migration of human gingival fibroblasts (HGFs) were examined in the presence and absence of nicotine by an in vitro study. Methods. The effects of different nicotine concentrations (1, 2, 3, 4, and 5 mM) on the viability and proliferation of HGF cells were evaluated in the presence and absence of different CC concentrations (5, 10, 25, and 50 μM) using the quantitative MTT assay. The scratch test was performed to evaluate the migration of CC-treated cells in the presence of 2.5-mM nicotine. Results. No cytotoxicity was observed at 1‒100 μM CC concentrations after 24, 48, and 72 hours of exposure to HGF cells. However, a concentration of 200 μM significantly reduced cell viability by about 20% at all the three-time intervals (P<0.05). Also, 3‒5-mM concentrations of nicotine significantly reduced cell viability in a dose- and time-dependent manner. Moreover, the understudied CC concentrations decreased nicotine’s adverse effects on cell migration to some extent. Conclusion. Although the understudied CC concentrations could not significantly reduce the adverse effects of understudied nicotine concentrations on the viability and proliferation of HGF cells, they were able to reduce the detrimental effects of nicotine on cell migration significantly.